Pendred syndrome: evidence for genetic homogeneity and further refinement of linkage. Issue 2 (February 1997) - Gausden, E; Coyle, B; Armour, J A; Coffey, R; Grossman, A; Fraser, G R; Winter, R M; Pembrey, M E; Kendall-Taylor, P; Stephens, D; Luxon, L M; Phelps, P D; et al.
Abstract : Pendred syndrome is the association between congenital sensorineural deafness and goitre. The disorder is characterised by the incomplete discharge of radioiodide from a primed thyroid following perchlorate challenge. However, the molecular basis of the association between hearing loss and a defect in organification of iodide remains unclear. Pendred syndrome is inherited as an autosomal recessive trait and has recently been mapped to 7q31 coincident with the non-syndromic deafness locus DFNB4. To define the critical linkage interval for Pendred syndrome we have studied five kindreds, each with members affected by Pendred syndrome. All families support linkage to the chromosome 7 region, defined by the microsatellite markers D7S501-D7S523. Detailed haplotype analysis refines the Pendred syndrome linkage interval to a region flanked by the marker loci D7S501 and D7S525, separated by a genetic distance estimated to be 2.5 cM. As potential candidate genes have as yet not been mapped to this interval, these data will contribute to a positional cloning approach for the identification of the Pendred syndrome gene.